Internal and external factors on firms' transfer pricing decisions: insights from organization studies - Li, Dan (2007)
Well understood in economics, accounting, finance, and legal research, transfer pricing has rarely been comprehensively explored in organization management literature. This paper explores some theoretical explanations of transfer pricing within multidivisional firms drawing insights from various organizational theories - primarily institutional theory, transaction cost economics, and social networks - to develop a conceptual model of transfer pricing. This model focuses on the nature of multidivisional firms' internal transfers, internal and external technological environments, and internal and external social environments. We highlight the importance of transfer pricing as a key strategic dimension to understand intra-firm flows and their associated costs.